Integration of Structural Knowledge in Design Studio Project: Assessment Study of Curriculum In Architecture Course in University Of Malaya - Aniza Abdul Aziz; Maha Mohani Fahmi; Lim Take Bane (Journal of Design and the Built Environment, 2010)
Architectural education should advance in parallel with the industrial growth of building technology. Universities as producers of future architects have yet to develop curriculums for building technology to suit the growth of the building industry. This gap between education and industrial growth has been a topic of debate for many researchers who are concerned about architectural pedagogy. Architectural instruction further aggravated the problem whereby in most architectural schools worldwide, teaching is divided between the design studio, where the design projects are taught and lecture classes where the technical parts are taught. The latter should be integrated with design studio to enhance design levels. Students face difficulty integrating and applying the structural knowledge gained from structure classes into their design. One explanation for this deficiency is because the current architectural structure subject's content is borrowed from an engineering syllabus. This study will examine the course content, instruction styles and method of teaching structure subjects and will investigate the learning outcomes of design studio through students' performance and perception in integrating structural knowledge in their design projects. Respondents were students from Year 1 to Year 5 doing their Bachelor of Science in Architecture and Bachelor of Architecture degrees in University of Malaya. Semi-structured interviews were conducted with the design studio coordinators and structure lecturers. This study aims to find the ideal course content/method of teaching to facilitate more integration between structure and design studio.